Incidence of Cerumen Impaction Among School-Age Children at the Durenan Primary Public Healthcare Working Area in 2025 - Restu Kaharseno; Garnis Nirwan; Ani Shofiani (Riviera Publishing, 2026)
Hearing loss is a global health concern affecting more than 5% of the world’s population, with cerumen impaction being one of the leading causes of conductive hearing loss, particularly among children. This study aimed to determine the incidence of cerumen impaction among school-age children in the Durenan Primary Public Healthcare working area in 2025. This was a descriptive qualitative study using secondary data obtained from hearing health screenings conducted in 22 elementary schools, 5 junior high schools, and 7 senior high schools within the healthcare center’s service area. The screenings were performed using otoscopic and headlamp examinations. The results showed that 376 elementary school students (20.15%), 159 junior high school students (12.58%), and 215 high school students (7.53%) experienced cerumen impaction, indicating a higher prevalence among younger age groups. These findings were consistent with previous research in Indonesia, which reported cerumen impaction rates of 30.5% among school-age children, with higher incidence among elementary school students compared with older age groups. The findings highlight the need to strengthen public health education, particularly for parents and school communities, regarding appropriate ear hygiene practices and the risks associated with cotton bud use. Furthermore, routine school-based ear screenings are recommended as an early detection and prevention strategy.